Effect of fruit maturity on the quality and acceptability of guava purée - Yusof, Salmah; Mohamed, Suhaila; Abu Bakar, Abdullah (1988)
A study was conducted to determine the characteristics of guava fruits and the purée obtained from fruits at six stages of maturity, i.e. stage 1: fruits 14 weeks after inception; stage 2: 15 weeks after inception; stage 3: 16 weeks after inception; stage 4: fruits artificially ripened in 1000 ppm ethylene for 1 1 2 days; stage 5: similar fruits ripened for 2 1 2 days in ethylene; stage 6: similar fruits ripened for 3 days in ethylene. The hardness of the fruits decreased as they matured and ripened. Moisture increased in the first three stages and slowly declined up to stage 6. The pH, titratable acidity and sugars showed similar decreasing trends up to stage 4 and increased thereafter. The tannin content decreased with increasing fruit maturity. The Brix-acid ratio was highest (16·3) at stage 4. Ascorbic acid showed a sigmoid pattern of increase in values up to stage 4 and thereafter decreased. Evaluation of the purée showed increasing viscosity with increase in fruit maturity. The increase in viscosity was possibly due to increase in amount of soluble pectin (which was highest in stage 4). Cellulose content of guava decreased as the fruits ripened. The amount of protopectin also decreased as the fruits softened. Colours of purées from stage 4 onwards seemed to be less susceptible to browning and were, in fact, improved after addition of sugar. Sensory analysis indicated high preference for samples in stages 2, 3 and 4 but there was no significant difference in flavour among the three samples. Based on these physical and chemical characteristics, fruits from stage 4 were considered to be most suitable for processing into purée. © 1988.